Contextual Effect of Community Health Center on Visual Inspection Acetic Acid Uptake in Magelang, Central Java: A Multilevel Analysis - Martaningrum, Herlina Ika; Budihastuti, Uki Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2020)
Background: Cervical cancer is a major problem in women's. Cervical cancer can be prevented by early examinations i.e. visual inspection acetic acid (VIA). This study aimed to analyze the contextual effect of community health center on VIA uptake in Magelang, Central Java.Subjects and Method: This was analytic observational study with cross-sectional design. The study was conducted at 25 community health centers in Magelang, Central Java, from September to October 2019. A total sample of 200 women aged 30 to 50 years was selected randomly. The dependent variable was VIA uptake. The independent variables were knowledge, observational learning, behavioral reinforcement, cues for action, access to information, family support, attitude, self-efficacy, outcome expectation, and contextual factor of community health center. The data were collected by questionnaire and analyzed by a multilevel multiple logistic regression run on Stata 13.Results: VIA uptake increased with good knowledge (b= 4.02; 95% CI= 0.61 to 7.42; p= 0.021), observational learning (b= 2.28; 95% CI= -0.35 to 4.93; p= 0.090), strong behavioral reinforcement (b= 4.11; 95% CI= 0.82 to 7.40; p= 0.014), strong cues to action (b= 5.36; 95% CI= 0.65 to 10.07; p= 0.026), good access to information (b= 3.71; 95% CI= 0.42 to 7.01; p= 0.027), strong family support (b= 4.23; 95% CI= 0.21 to 8.25; p= 0.039), positive attitude (b= 3.29; 95% CI= -0.23 to 6.81; p= 0.067), strong self-efficacy (b= 2.94; 95% CI= 0.10 to 5.78; p= 0.042), and strong outcome expectation (b= 3.39; 95% CI= 0.35 to 6.44; p= 0.029). Community health center had strong contextual effect on VIA uptake with intra-class correlation (ICC)= 23%.Conclusion: VIA uptake increases with good knowledge, observational learning, strong behavioral reinforcement, strong cues to action, good access to information, strong family support, positive attitude, strong self-efficacy, and strong outcome expectation. The community health center has a strong contextual effect on VIA uptake.Keywords: visual inspection acetic acid, social cognitive theory, multilevel analysisCorrespondence: Herlina Ika Martaningrum, Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: herlinaika21@gmail.com. Mobile: 085643528156Journal of Maternal and Child Health (2020), 5(2): 129-140https://doi.org/10.26911/thejmch.2020.05.02.02